Analisis Kualitas Layanan Terhadap Loyalty Behavior ada Aplikasi SRIBU Menggunakan Metode E-Servqual - Faiz Rizki Saputra; Bayu Waspodo; Evy Nurmiati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The phenomenon of low app ratings and technical complaints on the Google Play Store became the background of this main research to expand which service quality dimensions are able to maintain the user base. The method used is E-SERVQUAL which includes seven dimensions: Efficiency, System Availability, Fulfillment, Privacy, Responsiveness, Contact, and Compensation. Data were collected through questionnaires from 405 respondents who use the SRIBU Mobile application and analyzed using the Partial Least Square-Structural Equation Modeling approach through SmartPLS software. The results showed that the aggregate service quality was assessed as good with an average value of 1.0379. The results of hypothesis testing confirmed that the dimensions of Efficiency, System Availability, Fulfillment, Privacy, Responsiveness, and Contact have a significant effect on user satisfaction. Furthermore, user satisfaction was proven to have a very strong positive and significant influence on loyalty behavior with a path coefficient value of 0.875. However, the Compensation dimension was found to have no significant influence on satisfaction. In addition, the Contact and Compensation dimensions showed poor values ​​indicating that there are aspects of the service that have not met user expectations. This study recommends that PT SRIBU Digital Kreatif prioritize improvements to customer support channels and compensation policies to minimize service failures and strengthen user loyalty amidst intense digital economic competition.